2008
DOI: 10.1007/s00018-008-8170-7
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of mitogen-activated protein kinases (MAPKs) made simple

Abstract: The mitogen-activated protein kinase (MAPK) pathways are known to be involved in various processes of growth, differentiation and cell death. In spite of their ubiquitous presence and seemingly enormous cross-talk with each other, their action is very specific. This review deals with various aspects of the three different MAPK pathways (ERK, p38 and JNK) and how their specificity is brought about.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
330
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(333 citation statements)
references
References 224 publications
(216 reference statements)
3
330
0
Order By: Relevance
“…The MAPK pathways are classically divided into the ERK, JNK, and p38 pathways (48). To determine which MAPK signaling pathway may be involved in the regulation of integrin ␤8 expression through AP-1, primary adult lung fibroblasts were treated with chemical inhibitors to each of these pathways then analyzed for surface expression of integrin ␤8 using flow cytometry (Fig.…”
Section: Ap-1 Complexes Bind To the Putative Cre Binding Site In The mentioning
confidence: 99%
“…The MAPK pathways are classically divided into the ERK, JNK, and p38 pathways (48). To determine which MAPK signaling pathway may be involved in the regulation of integrin ␤8 expression through AP-1, primary adult lung fibroblasts were treated with chemical inhibitors to each of these pathways then analyzed for surface expression of integrin ␤8 using flow cytometry (Fig.…”
Section: Ap-1 Complexes Bind To the Putative Cre Binding Site In The mentioning
confidence: 99%
“…It is widely believed that activation of MAPK pathways, in particular the extracellular signal-regulated kinase (ERK) 1 and 2 (p44 and p42 MAPKs), contributes to cell proliferation [27] . We previously showed that ERK activation is one of the prerequisites for continuous proliferation of the C2C12 myoblasts [18] .…”
Section: Bupivacaine Inhibits Proliferation Via Erk Pathwaymentioning
confidence: 99%
“…Multiple MAPK signaling cascades can be activated by a variety of stimuli, allowing the cells to respond coordinately to multiple and divergent inputs [27] . The ERK pathway has been believed to be a central regulator of cell proliferation by controlling cell growth and cell cycle progression [27,39] . In the muscle cell model system (C2C12), we previously reported that activation of ERKs is one of the prerequisites for continuous myoblast cell growth [18] .…”
Section: Wwwnaturecom/aps Maurice Jm Et Almentioning
confidence: 99%
“…Once activated, MAPK can affect a number of cytosolic components through its proline-directed serine/threonine activity, or it can translocate to the nucleus where it can phosphorylate and activate a number of transcription factors involved in immediate early gene expression (29)(30)(31). MAPKs are inactivated by a variety of dual-specificity phosphatases called MAP kinase phosphatases or MKPs.…”
Section: Mapk Family Treementioning
confidence: 99%
“…In addition, activated ERK1 and ERK2 can translocate to the nucleus, where they can phosphorylate transcription factors such as Elk-1, SAP-1, c-Myc, and ATF-2 (29)(30)(31)39).…”
Section: Mapk Family Treementioning
confidence: 99%